2016
DOI: 10.1038/ejhg.2015.266
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of PTHLH causes osteochondroplasia with a combined brachydactyly type E/A1 phenotype with disturbed bone maturation and rhizomelia

Abstract: Parathyroid hormone-like hormone (PTHLH, MIM 168470) plays an important role in endochondral bone development and prevents chondrocytes from differentiating. Disease-causing variants and haploinsufficiency of PTHLH are known to cause brachydactyly type E and short stature. So far, three large duplications encompassing several genes including PTHLH associating with enchondromatas and acro-osteolysis have been described in the literature. Here, we report on a three-generation pedigree with short humerus, curved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…These conditions include Jansen type metaphyseal dysplasia or neonatal onset hyperparathyroidism, which show cortical thinning, metaphyseal dysplasia, and pathological fractures on plain X‐rays (Al‐Khalaf, Ismail, Soliman, Cole, & Ben‐Omran, ; Charrow & Poznanski, ). Similar findings have also been observed in individuals with PTHLH duplications (Collinson et al, ; Flöttmann et al, ; Gray et al, ).…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…These conditions include Jansen type metaphyseal dysplasia or neonatal onset hyperparathyroidism, which show cortical thinning, metaphyseal dysplasia, and pathological fractures on plain X‐rays (Al‐Khalaf, Ismail, Soliman, Cole, & Ben‐Omran, ; Charrow & Poznanski, ). Similar findings have also been observed in individuals with PTHLH duplications (Collinson et al, ; Flöttmann et al, ; Gray et al, ).…”
Section: Introductionsupporting
confidence: 80%
“…Several different groups have reported skeletal anomalies caused by the duplication of PTHLH . The smallest duplication reported that only contained PTHLH and no other known genes has been found to result in short humeri, curved radii, and brachydactyly (Flöttmann et al, ). Larger reported duplications by two other groups which also included additional genes had more severe presentations with the presence of acro‐osteolysis and enchondromatas (Collinson et al, ; Gray et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTHLH regulates endochondral bone development and epithelial mesenchymal interaction. Flöttmann et al reported that duplication of PTHLH causes osteochondroplasia [74]. Since Borras and colleagues suggest that the pathological changes in the POAG TM resembles calcification [75], a down-regulation of PTHLH in the non-responder group may help to explain why their TM is less effected by DEX.…”
Section: Discussionmentioning
confidence: 99%
“…A high incidence of carpal tunnel syndrome has been observed in patients with PHP1A and PPHP (67% of patients with PHP1A reported symptoms versus 15% of the general population) 253 . Additional skeletal features have been described in different disorders of the PTH-PTHrP pathway, such as Madelung deformity 72,128 , spinal stenosis 203,[254][255][256][257] , acroosteolysis, cortical irregularity of long bones and metadiaphyseal enchondromata or short humerus and curved radius 258 , as well as other craniofacial peculiarities (typical pear-shaped nose, long and flat philtrum, thin upper lip and receding chin) and phalangeal cone-shaped epiphyses, resulting in clinodactyly 259 . Depending on the functional consequences, the patient might require corrective orthopaedic surgery.…”
Section: Brachydactyly and Orthopaedic Issuesmentioning
confidence: 99%